True
False
The factor of the expression 8r⁶ + 27s¹² can be (2r²+3s⁴)(4r⁴-6r²s⁴+9s⁸) after using the identity a³+b³ = (a+b)(a²-ab+b²).
It is defined as the combination of constants and variables with mathematical operators.
It is given that:
= 8r⁶ + 27s¹²
The above expression can be written as:
8r⁶ + 27s¹² = (2r²)³+(3s⁴)³
After applying the identity:
a³+b³ = (a+b)(a²-ab+b²)
= (2r²+3s⁴)(4r⁴-6r²s⁴+9s⁸)
Thus, the factor of the expression 8r⁶ + 27s¹² can be (2r²+3s⁴)(4r⁴-6r²s⁴+9s⁸) after using the identity a³+b³ = (a+b)(a²-ab+b²).
Learn more about the expression here:
#SPJ5
Answer:
a^3+b^3=(a+b)(a²-ab+b²)
8r^6+27s^12=(2r²)^3+(3s^4)^3=(2r²+3s^4)(4r^4-6r²*s^4+9s^8)
B. 50 degrees
C. 0 degrees
plzzzz help its due now...
I think it´s all of them except 1.33
Answer:
23, 69 and 123
Step-by-step explanation:
let the first number be x then the second number is 3x ( 3 times the first) and the third number is x + 100 ( 100 more than the first number)
The sum of the three numbers is
x + 3x + x + 100 = 215
5x + 100 = 215 ( subtract 100 from both sides )
5x = 115 ( divide both sides by 5 )
x = 23
The 3 numbers are
x = 23, 3x = 3 × 23 = 69 and x + 100 = 23 + 100 = 123